Advances in dairy ingredients - Smithers, Geoffrey W.; Augustin, M. A. (Institute of Food Technologists series., 2013)
Advances in Dairy Ingredients provides an international perspective on recent developments in the area of dairy ingredients and dairy technology. Market and manufacturing trends and opportunities are aligned with the latest science tools that provide the foundation to successfully and rapidly capture these opportunities. Functional foods are emerging as key drivers of the global food economy and dairy ingredients and technology are at the forefront in these developments. Advances in Dairy Ingredients brings together food scientists, industry specialists, and marketers from around.